Metabolic Profiling Indicates Diversity in the Metabolic Physiologies Associated With Maternal Postpartum Depressive Symptoms - Bränn, Emma; Malavaki, Christina; Fransson, Emma; Ioannidi, Maria-Konstantina; Henriksson, Hanna E.; Papadopoulos, Fotios C.; Chrousos, George P.; Klapa, Maria I.; Skalkidou, Alkistis (Frontiers in Psychiatry, 2021)
Background: Postpartum depression (PPD) is a devastating disease requiring improvements in diagnosis and prevention. Blood metabolomics identifies biological markers discriminatory between women with and without antenatal depressive symptoms. Whether this cutting-edge method can be applied to postpartum depressive symptoms merits further investigation. Methods: As a sub-study within the Biology, Affect, Stress, Imagine and Cognition-study, 24 women with PPDS assessment at 6 weeks postpartum were included. Controls were selected as having a score of ≤6 and PPDS cases as ≥12 on the Edinburgh Postnatal Depression Scale. Blood plasma was collected at 10 weeks postpartum and analyzed with GC-MS metabolomics. Results: Variations of metabolomic profiles within the PPDS samples were identified. One cluster showed altered kidney function while the other a metabolic syndrome profile, both previously associated to depression. Five metabolites (glycerol, threonine, 2-hydroxybutanoic acid, erythritol, and phenylalanine) showed higher abundance among women with PPDS, indicating perturbations in the serine/threonine and glycerol lipid metabolism, suggesting oxidative stress conditions. Conclusions: Alterations in certain metabolites were associated with depressive pathophysiology postpartum, while diversity in PPDS physiologies was revealed. Hence, plasma metabolic profiling could be considered in diagnosis and pathophysiological investigation of PPD towards providing clues for treatment. Future studies require standardization of various subgroups with respect to symptom onset, lifestyle, and comorbidities.